Reverse cardio-oncology: is heart failure-mediated gut dysbiosis the mechanistic driver of colorectal cancer progression? - Rangrez, Ashraf Yusuf; Frey, Norbert (Cardiovascular research, 2024)
This editorial refers to ‘Heart failure-induced microbial dysbiosis contributes to colonic tumour formation in mice’, by S. de Wit et al., https://doi.org/10.1093/cvr/cvae038.Cardiac diseases and cancer are major health burdens and leading causes of mortality worldwide. Great efforts in past decades revolutionized cancer therapy options that reduced mortality and morbidity associated with different cancers.1 However, it has also been evident that the patients with anti-cancer therapy are more prone to develop cardiovascular diseases due to what is referred to as ‘cardiotoxicity’ of anti-cancer treatments. For example, anthracyclines, a commonly used anti-cancer medication, has been extensively studied for its cardiotoxicity.2 This evolved into a concept of ‘cardio-oncology’, where cardiologists and oncologists work together to develop optimal strategies for patient care during or even beyond cancer treatment to contain cardiovascular disease development/progression. Though cancer and cardiovascular disease are currently viewed as distinct entities, our advancement in understanding the underlying mechanisms reveals that both these disease conditions share mutual risk factors such as chronic inflammation, diabetes, obesity, smoking, alcohol consumption, etc., suggesting that cancer and cardiovascular diseases may also share common molecular pathways.3 Moreover, it has been proposed that a reciprocal link between cardiovascular diseases and cancer exists, where patients with cardiovascular disease are at higher risk of developing cancer than the healthy individuals, which gave rise to a field coined ‘reverse cardio-oncology’.3 We are, however, still far from understanding how exactly existing cardiovascular disease may promote the development of cancer. In this issue of Cardiovascular Research, de Wit et al.,4 using a mouse model of heart failure (HF), provide insight into how HF-driven gut microbial alterations, also termed as ‘gut dysbiosis’, contribute to colonic tumour formation. Gut dysbiosis has earlier been linked with the progression of colorectal and other forms of cancers.5,6 Conversely, several studies have demonstrated an association between HF and gut dysbiosis.7 Based on these observations, de Wit et al. hypothesized that HF-induced gut microbial dysbiosis may stimulate colorectal tumour formation.
Veröffentlicht: 28. März 2024
Gesehen am 13.08.2024